Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Pada Pembelajaran Matematika Di Kelas Vii Smpn 1 Lareh Sago Halaban Berdasarkan Tahapan Newman - Adewiani, Melantika; Rahmat, Tasnim; Fitri, Haida (Universitas PGRI Semarang, 2023)
This study aims to analyze student errors in solving word problems in mathematics learning. One way that can be used to find out why this happened is by analyzing students' mistakes in solving word problems in mathematics learning based on Newman's stages in class VII SMPN 1 Lareh Sago Halaban. This research is a qualitative descriptive study. Data collection was carried out by collecting students' daily test results for analysis based on Newman's stages and interviews. The research subjects in this study were taken from students in class VII SMPN 1 Lareh Sago Halaban. The research subjects were taken based on the number of subjects making mistakes from the results of students' daily tests. Each research subject was interviewed regarding the results of his work in solving math word problems based on Newman's stages. Data validity test was carried out by technical triangulation.The results showed that the subject made mistakes at the stages of understanding, transforming, processing ability and writing the final answer due to carelessness and lack of understanding of the subject's mathematical concepts.